Rubbing Massage Provides Good Evidence in Reducing Pain in the First Stage of Labor - Sumarni Sumarni; Siti Fadlilah (Jurnal Keperawatan Respati Yogyakarta, 2023)
Pain is a common complaint felt by mothers during labor. Massage can be used as an intervention to reduce labor pain. The study contributes to determining the effect of rubbing massage on pain in the first phase of active labor in Pekalongan City. This quantitative research uses a quasi-experiment approach with a pretest and posttest without a control group design. The population was the first phase of active maternity mothers in Pekalongan, Central Java, Indonesia, in September-November 2017. Samples of 21 mothers were taken using purposive sampling. Statistical tests use the Wilcoxon test. Most respondents of the young age category (> 26 years) are 12 mothers (57%). Respondents had the most junior high school education of 9 mothers (43%). The median of the pretest pain was six, and the posttest pain was 5. The bivariate results obtained a p-value of 0,000. The results showed that rubbing massage effectively reduces pain in first-phase active mothers.